Pengembangan Rantai Pasok Daging Ayam secara Terpadu di Jawa Barat dan Jawa Timur - nFN Saptana; Nyak Ilham (Analisis Kebijakan Pertanian, 2020)
The main problem faced by the broiler industry from time to time was its vulnerability to various large and short-term shocks. This study aimed to assess and formulate policy recommendations for the development of the supply chain integration of chicken meat. The analytical methods used in this study were the supply chain, market integration, and price fluctuation analysis. The results of this study indicated that supply chain actors in live broiler commodities and chicken meat were still quite long and less competitive. The dominant position in determining prices in the chicken meat supply chain was integrator companies and collectors. Broiler market integration at the farm level in the production center in West Java and the retailer level in the City of Bandung was not well integrated with the Market Index Connection (IMC) value of 5.956 (not integrated) and in East Java was also not integrated but with better the IMC value of 1.654. The level of chicken meat price fluctuations was quite moderate, as indicated by the Coefficient of Variation (CV) value 6.82. Broiler prices at the producer level were more volatile than the price of chicken meat at the consumer level. Policy implications drawn from this study are the need to cut the very long supply chain, improve the market structure towards a more competitive one, increase market integration, and maintain stabilization of chicken meat prices. AbstrakPermasalahan pokok yang dihadapi industri broiler dari waktu ke waktu adalah kerawanannya terhadap terhadap berbagai goncangan besar dan berjangka pendek. Penelitian ini bertujuan untuk mengkaji dan menghasilkan rekomendasi kebijakan pengembangan rantai pasok daging ayam ras secara terpadu.Metode analisis yang digunakan adalah analisis rantai pasok, integrasi pasar, dan fluktuasi harga. Hasil penelitian ini menunjukkan pelaku rantai pasok pada komoditas broiler hidup dan daging ayam masih cukup panjang dan kurang kompetitif. Posisi dominan dalam penentuan harga pada rantai pasok daging ayam adalah perusahaan integrator dan pedagang pengepul. Integrasi pasar broiler di tingkat peternak di daerah sentra produksi di Jawa Barat dan di tingkat pedagang pengecer di Kota Bandung tidak terintegrasi dengan baik dengan nilai Index Market Conection (IMC) sebesar 5,956 (tidak terintegrasi), dan di Jawa Timur juga tidak integrasi namun dengan nilai IMC yang menunjukkan lebih baik, yaitu  1,654. Tingkat fluktuasi harga daging ayam cukup moderat, yang diindikasikan oleh nilai Coefisien Variasi (CV) 6,82. Harga broiler di tingkat produsen lebih fluktuatif dibandingkan harga daging ayam ras di tingkat konsumen. Implikasi kebijakan dari temuan penelitian ini adalah perlunya memotong rantai pasok yang terlalu panjang, memperbaiki struktur pasar ke arah struktur yang lebih kompetitif, meningkatkan keterpaduan pasar dan menjaga stabilisasi harga daging ayam.